Melaut, Mengasuh, dan Bertahan: Narasi Gender dalam Adaptasi Perempuan terhadap Krisis Iklim - Asterlita Tirsa Raha; Mia Siscawati (Jurnal Kajian Gender dan Anak, 2025)
The climate crisis is not merely an environmental issue; rather, it is a manifestation of systemic inequality that exacerbates social and gender disparities, particularly in coastal regions. In Morodemak Village, Demak, Central Java, tidal flooding has become a recurring ecological disaster with significant ramifications for the local population, particularly women. The consequences of these challenges are particularly pronounced for women, who often experience physical exhaustion from reproductive work, skin infections due to contaminated water, and mental distress from dual responsibilities and inadequate structural support. The objective of this study is to elucidate how women's bodies function as epistemic spaces in response to the climate crisis, as well as how women's agency manifests through collective solidarity in the context of minimal state presence. The methodological approach is qualitative, employing an intrinsic case study design. The study's design encompasses the following methods: in-depth interviews, focus group discussions (FGDs), participatory observation, and body-territory mapping. The informants consist of adult and elderly women who have experienced the direct impact of tidal flooding and are involved in community adaptation practices. The findings indicate that women in Morodemak encounter a multitude of vulnerabilities, yet they have cultivated adaptive capacities through community organizations such as Puspita Bahari. The state's regulatory approach is considered negligent, as it does not formally recognize tidal flooding as a disaster. This oversight has resulted in policies that demonstrate a lack of consideration for the needs of affected individuals and communities. This study underscores the importance of acknowledging women's bodily experiences as a foundation for designing fair and participatory climate policies